Promotion of Hope in Patients Cared for in an Intensive Care Unit in Indonesia. (March 2013) - da Silva, Jenny Milton; Henricson, Maria
Aim and objective: The aim was to describe the nurses' perception about how to promote hope in critically ill patients, cared for in intensive care units in Indonesia. Background: The concept of hope and hopelessness has been in focused in nursing from various orientations as a subjective phenomenon in relation to illness experiences. There is a lack of studies examining patterns of how nurses promote hope in critically ill patients in intensive care. Design and Method: Five specialized intensive care nurses from two different intensive care units were interviewed. The interviews were analysed according to a qualitative content analysis. Results: The patient's hope is something personal and depends on different factors. These factors can either be a supporting system or an inhibiting factor to the nurse's illumination of hope. Meaning, if something is very important for the patient (i.e. the family), there can be a radical difference if that person is present and supporting, present and not supporting or even not present at all. Conclusion: By using interventions including information, communication and religion, the nurses may release hope within the patient. This hope can be cultural and socially bound but it does not avoid the facts of the promotion that can be tailored by the nurses to individual circumstances and possibly used in other wards but also in different countries.